Policy Implications of "Second-Generation" Crisis Models - Marion, Nancy; Flood, Robert (Washington, D.C. : International Monetary Fund, 1997)
After the speculative attacks on government-controlled exchange rates in Europe and in Mexico, economists began to develop models of currency crises with multiple solutions. In these models, a currency crisis occurs when the economy suddenly jumps from one solution to another. This paper examines one of the new models, finding that raising the cost of devaluation may make a crisis more likely. Consequently, slow convergence to a monetary union, which increases the cost to the government of reneging on an exchange rate peg, may be counterproductive. This conclusion is exactly the opposite of that obtained from earlier models.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Mexico